Mild hyperthermia inhibits homologous recombination, induces BRCA2 degradation, and sensitizes cancer cells to poly (ADP-ribose) polymerase-1 inhibition - Krawczyk, Przemek M; Eppink, Berina; Essers, Jeroen; Stap, Jan; Rodermond, Hans; Odijk, Hanny; Zelensky, Alex; van Bree, Chris; Stalpers, Lukas J; Buist, Marrije R; Soullié, Thomas; Rens, Joost; et al. (Proceedings of the National Academy of Sciences - PNAS, 2011)
Defective homologous recombination (HR) DNA repair imposed by BRCA1 or BRCA2 deficiency sensitizes cells to poly (ADP-ribose) polymerase (PARP)-1 inhibition and is currently exploited in clinical treatment of HR-deficient tumors. Here we show that mild hyperthermia (41-42.5 °C) induces degradation of BRCA2 and inhibits HR. We demonstrate that hyperthermia can be used to sensitize innately HR-proficient tumor cells to PARP-1 inhibitors and that this effect can be enhanced by heat shock protein inhibition. Our results, obtained from cell lines and in vivo tumor models, enable the design of unique therapeutic strategies involving localized on-demand induction of HR deficiency, an approach that we term induced synthetic lethality.